Tuberculous retropharyngeal abscess presenting as severe dyspnea - Lame, Cheikh Ahmedou; Loum, Birame; Ndiaye, Cheikhna Ba; Diop, Sagar; Diop, Moustapha; Kone, Madjiguene (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Tuberculous retropharyngeal abscess is an exceptional condition, with high potential of functional morbidity and mortality if not treated appropriately. The authors report a new case of airway obstructive retropharyngeal abscess revealing cervical Pott disease. A 59 years old man presented at Ear, neck and throat (ENT) department with severe acute dyspnea. The history revealed progressive chronic dysphagia associated with asthenia and important weight loss. Physical examination found a state 3 dyspnoeic patient, presenting hyper flexed neck with limited movements. Nasofibroscopy showed a huge retropharyngeal bulge. Computed tomography (CT) scan showed a large retropharyngeal abscess located in front of vertebral spondylodiscitis with anterior dislocation of C4-C5-C6 vertebrae. Trans-oral incision with drainage of the retropharyngeal abscess was performed under general anaesthesia. Bacteriologic assessment of the pus confirmed tuberculosis infection. Anti-tuberculous medication was delivered, associated with spinal stabilization by a rigid cervical collar. Tuberculous retropharyngeal abscess is a very rare condition. Early diagnosis and treatment are necessary to prevent neurological and life-threatening complications. Collaboration between ENTs, anaesthetists, neurosurgeons and infectious disease specialists remains incontournable.